∫ − 1 5 ( 1 + x ) ( 2 x + x 2 ) 5 d x = ?
Note :You can use calculator at final step of your calculation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution.What most people forget to do is that when you are taking substitution , since it is definite integration the limits will also change according to the substitution.Upvoted your solution
Log in to reply
Yeah....you are correct :-)
Log in to reply
Ive comitted so many countless mistakes and this is one of them.Thats why I take caution before solving any question.
Log in to reply
@Athiyaman Nallathambi – Yeah.....I also do a lot of mistakes and very few times I really learn from them ..... very few ^_^
to avoid those mistakes i always substitute u back to original
that is u to 2x+x^2
Log in to reply
Even I do the same.
Look at my solution now.
∫ − 1 5 ( 1 + x ) ( 2 x + x 2 ) 5 d x
Let ( 2 x + x 2 ) = u ,
⇒ ∫ − 1 5 ( 1 + x ) ( 2 x + x 2 ) 5 d x
⇒ ∫ − 1 5 ( 1 + x ) u 5 d x
Now we can re-write it as ,
⇒ ∫ − 1 5 2 ( 1 + x ) 1 ( 1 + x ) u 5 d x × d x d u
⇒ ∫ − 1 5 2 1 u 5 d u
⇒ 5 + 1 2 1 u 5 + 1 ] − 1 5
⇒ 1 2 1 u 6 ] − 1 5
Replacing u with ( 2 x + x 2 ) ,
⇒ 1 2 1 ( 2 x + x 2 ) 6 ] − 1 5
⇒ 1 2 3 5 6 − 1 2 − 1 6
⇒ 1 5 3 1 8 8 8 0 2
take 2x+x^2=t so it becomes as
integration[(t^5dt)/2]
Problem Loading...
Note Loading...
Set Loading...